Field emission of carbon nanotubes on anodic aluminum oxide template with controlled tube density - Chen, PL; Chang, JK; Kuo, CT; Pan, FM (My University, 2005)
The tube number density of aligned carbon nanotubes (CNTs) grown over the nanoporous anodic aluminum oxide (AAO) template can be directly controlled by adjusting the CH4/H-2 feed ratio during the CNT growth. We ascribe the variation of the tube density as a function of the CH4/H-2 feed ratio to the kinetic competition between outgrowth of cobalt-catalyzed CNTs from the AAO pore bottom and deposition of the amorphous carbon (a-C) overlayer on the AAO template. A pore-filling ratio of 18% to 82% for the nanotubes overgrown out of nanopores on the AAO template can be easily achieved by adjusting the CH4/H-2 feed ratio. Enhanced field emission properties of CNTs were obtained by lowering the tube density on AAO. However, at a high CH4 concentration, a-C by-product deposit on the CNT surface can degrade the field emission property due to a high energy barrier and significant potential drop at the emission site. (C) 2005 American Institute of Physics.